2017
DOI: 10.1126/science.aah6765
|View full text |Cite
|
Sign up to set email alerts
|

Extensive water ice within Ceres’ aqueously altered regolith: Evidence from nuclear spectroscopy

Abstract: The surface elemental composition of dwarf planet Ceres constrains its regolith ice content, aqueous alteration processes, and interior evolution. Using nuclear spectroscopy data acquired by NASA’s Dawn mission, we determined the concentrations of elemental hydrogen, iron, and potassium on Ceres. The data show that surface materials were processed by the action of water within the interior. The non-icy portion of Ceres’ carbon-bearing regolith contains similar amounts of hydrogen to those present in aqueously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
252
1
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 185 publications
(279 citation statements)
references
References 77 publications
21
252
1
5
Order By: Relevance
“…The FAE occur at a broad enough range of latitudes that lighting is unlikely to have biased their identification. The modest affinity of FAE to the southern hemisphere may be linked to the slight N/S asymmetry in near‐surface ice content inferred from GRaND data (Prettyman et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The FAE occur at a broad enough range of latitudes that lighting is unlikely to have biased their identification. The modest affinity of FAE to the southern hemisphere may be linked to the slight N/S asymmetry in near‐surface ice content inferred from GRaND data (Prettyman et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Up to nearly 10 4 computational molecules reside on the surface, the equivalent of about one week of supply. If outgassing rates are 0.003kg s −1 (Prettyman et al 2017), this amounts to up to 2 10 kg 3´o f water on the surface. Spread from the winter pole to a latitude of 83°( 10 10 m 2 ), its thickness is a monolayer.…”
Section: Model Resultsmentioning
confidence: 99%
“…Ceres has a crust rich in water ice (Prettyman et al 2017), and over time these molecules diffuse through the overlying porous layer, emerge on the surface, and continuously supply a water exosphere. Other chemical species could be occasionally delivered to the main belt (e.g., CO 2 ice from comet impacts) or percolate up from the interior (e.g., Ar-40 from decay of K-40).…”
Section: Potential Exospheric Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations in the UV hinting at escaping water (A'Hearn and Feldman 1992) were confirmed in the sub-mm with detections with the Herschel space telescope ). Using nuclear spectroscopy data acquired by NASA's Dawn mission, Prettyman et al (2017) analysed the elemental abundances of hydrogen, iron, and potassium on Ceres. They found that the regolith, at mid-to-high latitudes, contains high concentrations of hydrogen, consistent with broad expanses of water ice.…”
Section: Evidence For Water In Asteroidsmentioning
confidence: 99%